Understanding of the Causes and Psychological Dynamics of Students Skipping School (A Study Through Case Studies) - Ghozali Rusyid Affandi (Universitas Muhammadiyah Sidoarjo, 2013)
This research aimed to determine the causes of truancy in high school students and to understand the psychological dynamics of high school students were absent. To achieve the goal of these studies used the framework of the research question consists of 5 questions, among others: 1). What the causes of truancy in junior high school student, 2). How do parents in implementing parenting at home, 3). How do teachers in delivering the course material; 4) What is the influence of the peer group does truancy; 5). How psychological dynamics junior high school students who were truancy. Qualitative research method used is the case study that examines a single case, with one person subject to the criteria of the study subjects were teenagers who were educated at the Junior High School, was truant more than school provision, 12 - 14 years , male sex and living in Yogyakarta. This study took place in the one of junior high school in Yogyakarta. Data taken using in-depth interviews to subjects and informants, participant observation and field notes. From the analysis carried out it was found that the causes of truant behavior of the subject is 1) The influence of peers, 2) Personal subject it self; 3) Factors parenting from his parents; 4) Threatening and worried environment, 5) the school environment factors. And comorbid psychological dynamics truant behavior consists of three conditions, pre conditions (will do skipping school), while truant and after truant. In addition it also found participation behavior after truant period, the positive behavior in the form of the emergence of a sense of responsibility will backwardness lessons and negative behaviors such as lying to teachers and parents about causes of truant behavior.